Fischerei auf die wichtigsten nordostatlantischen Grundfischbestände 1998 - Schöne, Rüdiger (1999)
A short review of the actual assessments on the northeastatlantic groundfish stocks of cod, saithe, haddock, redfish and Greenland halibut provided by the ICES „Arctic Fisheries Working Group“is given. All these stocks are presently considered outside safe biological limits. For the first time since 5 years the cod stock is in an endangered situation, because the assessment was to optimistic and the TAC therefore set to high. According to the recent assessments necessary changes in the commercial fishery of the year 1998 off the Nowegian coast and in the Barent-Sea area are discussed. Information on distribution and fishery of cod, haddock, saithe and redfish is given.Biological investigations were carried out onboard the German factory trawler FMS „KIEL“ in January/March and September/ Occtober 1998 in order to collect data of the German fishery in that area. Aspects of length and age distributions, and stomach- and gonad investigation are represented. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.